[PP.17.07] DIFFERENCES IN BLOOD PRESSURE AND BLOOD PRESSURE VARIABILITY IN THE ACUTE PHASE OF LOBAR AND DEEP INTRACREBRAL HEMORRHAGE. (September 2016) - Korompoki, E.; Gill, D.; Manios, E.; Vemmou, A.; Spengos, K.; Zakopoulos, N.; Vemmos, K.
Abstract : Objective: Intracerebral hemorrhage (ICH) subtypes differ in underlying pathophysiology and outcome. Deep ICH is strongly associated with hypertension whereas lobar ICH in suspected to result mainly from cerebral amyloid angiopathy. However, little is known about acute blood pressure (BP) and blood pressure variability (BPV) in these different subtypes of ICH. Design and method: A total of 61 consecutive first-ever ICH patients registered in the Athens Stroke Registry underwent 24-hour ambulatory BP monitoring (ABPM) within 24 hours of haemorrhage onset. ICH was categorized based on topography, to deep and lobar. Stroke severity was measured using the National Institutes of Health Stroke Scale (NIHSS). Functional outcome was measured at 3 months using the modified Rankin Scale (mRS). BPV was defined as the standard deviation (SD) of blood pressure recordings made by ABPM. The Student's t-test and the Chi-square test were used to compare between the two ICH subtypes; continuous variables were tested for normal distribution; p < or = 0.05 was used to indicate statistical significance. Results: The study population consisted of 45 deep and 16 lobar ICH. No differences were observed in age, gender, HASBLED score, and history of hypertension, diabetes mellitus, smoking, and alcohol consumption between the two groups. Comparisons regarding stroke severity (NIHSS) and functional outcome (mRS) revealed no significant difference (p = 0.82 and p = 0.59, respectively). The mean systolic BP 24 h was significantly higher in the deep ICH group compared to the lobar ICH group (165 ± 16 vs 155 ± 16 mmHg, p = 0.04). Mean diastolic BP 24 h was also higher in patients with deep haemorrhage compared to those with lobar ICH (97 ± 14 vs 89 ± 15 mmHg, p = 0.05). No significant differences were observed between the two groups for systolic or diastolic BPV (p = 0.62 and 0.9, respectively). Conclusions: Mean systolic and diastolic BP during the first 24 hours of ICH is higher in deep as compared to lobar haemorrhage. Further research is needed in order to explore the association between BP with outcome in different ICH subtypes.